2001
DOI: 10.1007/s005950170135
|View full text |Cite
|
Sign up to set email alerts
|

Giant Mammary Hamartoma Diagnosed by Stereomicroscopic Analysis of the Mammary Glandular Tree in an Adolescent Girl: Report of a Case

Abstract: This report describes a rare case of a giant hamartoma that developed in the right breast of a 17-year-old girl. No abnormalities were found by endocrinological studies and a well-circumscribed tumor, approximately 20 cm in diameter, was easily enucleated without bleeding during surgery, following which the bilateral breasts became nearly symmetrical. Histologic features revealed predominant fibrous stroma and scattered normal or occasionally dysplastic mammary glands without neoplastic properties. No distorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…First described by Arrigoni et al 12 in 1971, mammary hamartomas were reported to comprise 0.7% of all benign tumours of the female breast 7 . They often present as painless mobile breast lumps in middle‐aged women 4,8,11 . Up to 66% of these lesions are soft and non‐palpable 1,4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First described by Arrigoni et al 12 in 1971, mammary hamartomas were reported to comprise 0.7% of all benign tumours of the female breast 7 . They often present as painless mobile breast lumps in middle‐aged women 4,8,11 . Up to 66% of these lesions are soft and non‐palpable 1,4 .…”
Section: Discussionmentioning
confidence: 99%
“…7 They often present as painless mobile breast lumps in middle-aged women. 4,8,11 Up to 66% of these lesions are soft and non-palpable. 1,4 These lesions may go unrecognized by the pathologists because they show all the constituents of normal breast tissue and may be reported as 'no pathological diagnosis' or 'normal breast tissue', which are inappropriate diagnoses for a lesion that presents as a palpable and a well-circumscribed mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation